Relation of the North to Slavery, A Discouse Preached in the Federal Meeting House, In Boston, On Sunday, June 11, 1854 - Gannett, Ezra S. (My University, 1854)
Gannett, Ezra S. Relation of the North To Slavery. A Discourse Preached in the Federal Street Meetinghouse, in Boston, on Sunday, June 11, 1854. Crosby, Nichols and Co. 1st, MDCCCLIC, dbd, 23 pgs., vg cond. $125.00
Keywords: Slavery; North; Sermon